Biologically inspired cognitive architectures 2010 : proceedings of the first Annual Meeting of the BICA Society - Samsonovich, Alexei V. (Frontiers in artificial intelligence and applications, 2010)
This book presents the proceedings of the First International Conference on Biologically Inspired Cognitive Architectures (BICA 2010), which is also the First Annual Meeting of the BICA Society. A cognitive architecture is a computational framework for the design of intelligent, even conscious, agents. It may draw inspiration from many sources, such as pure mathematics, physics or abstract theories of cognition. A biologically inspired cognitive architecture (BICA) is one which incorporates formal mechanisms from computational models of human and animal cognition, which currently provide the o.